The attraction of the Asian Giant: bilateral relations between Argentina and Brazil during the rise of China (2013-2015) - Actis, Esteban (2016)
The significant increase of political and economic interdependence, reached between Argentina and Brazil since 2003, began to suffer alterations in 2013. As in other historical times, the relative weakening of the bilateral relationship between Argentina and Brazil has one explanation (among many others): the changes in the international scene. However, this time is not due to the advance and co-optation strategy (the famous thesis of divide and rule) by Washington, but currently it ?s explained by China’s enlargement in the region.